A reusable anatomically segmented digital mannequin for public health communication. (2nd April 2016) - Fujieda, Kaori; Okubo, Kosaku
Abstract: The ongoing development of world wide web technologies has facilitated a change in health communication, which has now become bi-directional and encompasses people with diverse backgrounds. To enable an even greater role for medical illustrations, a data set, BodyParts3D, has been generated and its data set can be used by anyone to create and exchange customised three-dimensional (3D) anatomical images. BP3D comprises more than 3000 3D object files created by segmenting a digital mannequin in accordance with anatomical naming conventions. This paper describes the methodologies and features used to generate an anatomically correct male mannequin.